Board Diversity and Intellectual Capital Performance of Listed Non-Financial Service Firms in Nigeria - Tajudeen Lawal; Daniya Adeiza Abdulazeez; Musa Saidu (Universitas Negeri Semarang, 2022)
Purpose : This study examines the effect of board diversity on the intellectual capital performance of listed non-financial service firms in Nigeria. This is due to the paucity of studies in this area especially within the context of Nigeria even at the instance of the gradual and steady shift from the industrial to information/knowledge based economy.Method : The study employs correlational research design to examine the 44 sampled firms fora period of ten years (2011-2020). Quantitative data extracted from the annual reports of the firms were analysed using descriptive statistics, correlation and Fixed-Effects regressions.Findings : The regression results revealed that board composition and board size have significant positive effect on intellectual capital performance. However, board ownership has insignificant effect on intellectual capital performance. Consequently, the study failed to reject the second null hypothesis. Novelty : Previous Nigerian studies concentrated on the use of traditional Value Added Intellectual Coefficients (VAIC) which is currently considered inappropriate. Given the previous studies, this study is novel because it uses the Modified Value Added Intellectual Coefficient (MVAIC).Keywords : Board Diversity; Board Composition; Board Ownership; Board Size; Intellectual Capital Performance